Trade, development and resilience: an archaeology of contemporary livelihoods in Turkana, northern Kenya - Derbyshire, S (2017)
The recent history of the Turkana of northern Kenya has rarely been explored in detail, a fact that corresponds with, and to a large extent facilitates, their regular portrayal in the popular press as passive, unchanging and therefore vulnerable in the face of ongoing and ensuing socio-economic transformations. Such visions of the Turkana and the region in which they live have, via their manifestation in the policies and practices of development-orientated interventions, actively inhibited (although never fully arrested) the fulfilment of various local desires and aspirations over the years. In addressing these topics, this thesis provides some hitherto largely unexplored and unrecognised historical context to the many socio-economic and political issues surrounding Turkana’s ongoing development. It discusses interdisciplinary research which combined archaeological and ethnographic techniques and was undertaken amongst communities engaged in the most prominent livelihoods that have historically underlain the Turkana pastoral economy: fishing (akichem), cultivation (akitare), herding (akiyok) and raiding (aremor). In doing so, it draws attention to some of the ways in which these communities have actively and dynamically negotiated broad economic, environmental and political transformations over the last century and beyond, thereby providing a picture of social change and long-term continuity that might serve as a means for a more critical assessment of regional development over the coming years. By weaving together a series of historical narratives that emerge from a consideration of the changing production, use and exchange of material culture, the thesis builds an understanding of Turkana’s history that diverges from more standard, implicitly accepted notions of recent change in such regions of the world that envisage globalisation purely as a process of convergence or homogenisation. Its central argument, which it demonstrates using various examples, is that seemingly disruptive transformations in daily practices, social institutions, livelihoods and systems of livelihood interaction can be envisaged as articulations of longer-term continuities, emerging from a set of durable yet open-ended dispositions within Turkana society and culture. Moreover, rather than being built on a stable, passive repertoire of cultural knowledge, the thesis shows that this capacity for change is established upon a dynamic generative process where value systems and institutions are reconfigured to the same extent as daily practices and skills, as knowledge is continually reconstituted and recast in relation to the shifting constraints and possibilities of daily life. It thus characterises this process as a form of resilience that is deeply rooted in and determinant of the Turkana pastoral economy.